(untitled) (Journal of Institute of Science and Technology, 2025)
Bacterial co-infections and secondary infections in Coronavirus disease (COVID-19) patients can significantly worsen patient outcomes. Excessive use of antibiotics without prescription during viral infections might result in increase in antimicrobial resistance. This study aimed to determine the prevalence of these bacterial infections and assess multidrug resistance (MDR), Extended Spectrum β -Lactamases (ESBL) production, and biofilm formation among predominant isolates. A prospective study was conducted at Sukraraj Tropical and Infectious Diseases Hospital, Kathmandu, from July 2022 to June 2023. A total of 141 sputum samples from confirmed COVID-19 cases were processed using conventional culture methods. Antimicrobial susceptibility testing was done using the modified Kirby-Bauer Disc Diffusion method following Clinical Laboratory Standard Institute guidelines. Biofilm formation was detected by microtitre plate assay and ESBL production was confirmed phenotypically by the combined disc test. Deoxyribonucleic acid from ESBL-positive isolates was tested for the blaCTX-M gene using conventional polymerase chain reaction. Out of 141 patients, 9 (6.38%) showed bacterial co-infections and 11 (7.80%) showed secondary bacterial infections. Gram-negative bacteria were predominant, with Klebsiella pneumoniae 12 (60.00%) being the most common isolate. High resistance rates were observed in K. pneumoniae for Ceftriaxone 8 (66.70%) and Amikacin 7 (58.30%), while Imipenem remained effective for 11 (91.7%) isolates. Among the bacterial isolates 14/20 (70.00%) were MDR, 8/20 (40.00%) were biofilm producers and 8/19 (42.10%) were ESBL producers, with 6/8 (75.00%) harboring the blaCTX-M gene. To the best of our knowledge, this is one of the few studies to report ESBL producing MDR bacteria isolated from co-infection and secondary bacterial infection among COVID positive cases in Nepal. Continuous monitoring of bacterial infections and resistance patterns is crucial for improving infection control and managing the pandemic.